2019
DOI: 10.1155/2019/3926765
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Yield, Reaction to Diseases, and Grain Physical Attributes of Some Introduced Rice Hybrids in Ghana

Abstract: Hybrid rice technology is one of the promising, sustainable, and proven technologies for increasing rice production and productivity with a yield advantage of 15–30% over modern inbred varieties. The potential of hybrid rice has so far not been exploited in Ghana. This study was undertaken to evaluate the yield potential, reaction to diseases, and physical grain attributes of some introduced hybrids. The trials were laid out in a randomized complete block design (RCBD) with three replicates across three locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…Contrary, to succeptible rice lines, in the presence of these two types of RYMV the rice genotypes SK20-28 and Sim-simadel showed no significant inhibition in root growth. Abebrese et al (2019) indicated that some rice hybrids decrease the incidence of the RYMV disease and improve rice yield. So, they recommaded the introduction of these rice hybrids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary, to succeptible rice lines, in the presence of these two types of RYMV the rice genotypes SK20-28 and Sim-simadel showed no significant inhibition in root growth. Abebrese et al (2019) indicated that some rice hybrids decrease the incidence of the RYMV disease and improve rice yield. So, they recommaded the introduction of these rice hybrids.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the production losses, socio-economic impacts are caused by the disease across Africa, and the everincreasing resistance breakdown (Sereme et al, 2016); research activities continue mainly in the search for resistant varieties (Ndjiondjop et al, 1999;Albar et al, 2006;Thiémélé et al, 2010;Suvi et al, 2018), and few studies have been conducted to study how the virus affects the growth of the different parts of the plant to impact its production (Opalka et al, 1998;Abebrese et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The main tenet of hybrid rice technology is to employ the phenomenon of heterosis to out yield the available inbred semi-dwarf varieties. A yield advantage range of 15-20% over available inbred checks reported in other parts of the world has also been recorded in Africa [15,24,25,28]. Scaling up and promoting adopting of these hybrids, will contribute to food security in general on the African continent.…”
Section: Prospects Of Hybrid Rice In Africamentioning
confidence: 96%
“…Other National Agricultural Research systems (NARs) in collaboration with multi-national and local private seed companies also initiate their own in-country hybrid rice development and commercialization endeavor. For instance, NARS in Ghana in collaboration with international and local private seed companies (WIENCO, ADVANTA and SEED CO.) have conducted studies into farmer preferred traits and potential for adoption of hybrid rice [27] in Ghana, evaluated introduced rice hybrids for yield, rection to disease and grain quality attributes [28]. A study has also been conducted to identify CMS maintainers and restorers for local hybrid rice development [29].…”
Section: Strengthening the Capacity Of Partners On The Hybrid Rice Tementioning
confidence: 99%
“…Majority of the farmers as a result were expecting a minimum of 50% yield advantage over their currently grown variety to guarantee adoption of hybrid varieties. This expected yield advantage is quite huge since a yield advantage of 15-20% is currently possible (Abebrese et al, 2019;El-namaky & Demont, 2013;IRRI, 1997). Thus, the realizable yield advantage of hybrids will be a major determinant for adoption.…”
Section: Farmers' Knowledge and Willingness To Cultivate Hybrid Ricementioning
confidence: 99%